Islamic Education Strategies in Strengthening Character Education to Overcome Moral Challenges in the Digital Era - Naila Hanin Naswa; Muthoifin (Solo Universal Journal of Islamic Education and Multiculturalism, 2025)
Objective: The purpose of this study is to explore how character education can help overcome moral challenges arising from the use of digital technology and identify how to effectively integrate character education into the educational curriculum to form ethical attitudes and behaviors among students. Theoretical Framework: The theoretical framework used includes the concept of character education, which focuses on the formation of ethical values such as responsibility, empathy, and behavioral awareness in the context of the digital era. This theory also relates the role of character education in facing moral challenges caused by the development of digital technology. Literature Review: The literature review includes the theory of character education, previous research on the impact of character education on student behavior, and its application in a digital context. The literature also includes the study of moral challenges in the digital age, such as cyberbullying, the spread of false information, and social interaction in cyberspace. Methods: The research methods used are literature review and case analysis. A literature review includes a review of relevant theories and research, while a case analysis involves an evaluation of character education programs that have been implemented in several educational institutions, including their impact and outcomes on students. Results: The results of the study show that effective character education can increase students' awareness of ethical behavior, digital responsibility, and empathy. In addition, character education programs have been proven to reduce cases of cyberbullying, and the spread of false information, and improve the quality of social interaction in cyberspace. Implications: This study underscores the importance of integrating character values into the educational curriculum. A structured approach is needed to implement character education, so that it can have a positive impact on shaping students' ethical attitudes and behaviors, especially in facing moral challenges in the digital era. Novelty: The novelty of this research lies in the analysis of how character education can directly help students face specific moral challenges that arise as a result of the development of digital technology. This research also provides new insights into the success of character education programs in reducing problems such as cyberbullying and false information.